Improving Energy Conservation Using Six Sigma Methodology at Faculty of Computer and Mathematical Sciences (FSKM), Universiti Teknologi Mara (UiTM), Shah Alam - Razali, Nur Hidayah binti Mohd; Afthanorhan, Wan Mohamad Asyraf Bin Wan (Asian Journal of Economic Modelling, 2014)
Electrical consumption is increasing rapidly in Malaysia due to the sustenance of a modern economy way of living. Recently, the Vice Chancellor of University Technology MARA, Tan Sri Dato’ Professor Ir Dr Sahol Hamid Abu Bakar has shown a great deal of concern regarding the high electrical energy consumption in UiTM’s main campus in Shah Alam. This study seeks to evaluate the factors that contribute to high electrical energy consumption in the Faculty of Computer and Mathematical Sciences (FSKM), UiTM using the Six Sigma methodology and to compare electrical energy consumptions before and after the EC (Energy Conservation) initiative campaign. Many companies worldwide continue to achieve improvements in business performance using the Six Sigma approach. The electrical consumption from January 2011 until December 2013 was analyzed using five stages of Six Sigma which is Define, Measure, Analyze, Improve and Control (DMAIC). The total electrical consumption for 2011 was 1, 648, 791 kwH (RM 514,422.79) and 1, 657, 808 kwH (RM 517, 236.10) in 2012 which is an increase of 0.5% (RM 2813.31 or 9017 kwH). From the results obtained, Pareto chart shows that air-conditioner (57%) is the major factor that contributes to high consumption of electricity, followed by lightings (22%), sockets (16%) and others (5%). The electrical consumption was almost doubled when the new semester begun. After the campaign, there was a reduction of 2% in electrical consumption. This study has successfully implemented Six Sigma methodology which involves a systematic DMAIC process to evaluate electrical consumption in FSKM.